2014
DOI: 10.1590/1983-1447.2014.01.37821
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vaccination in the reduction of hepatitis B in Paraná

Abstract: This study identified the impact of hepatitis B vaccine over reducing incidence of this disease in Paraná State, between 2001 and 2011, and discussed the role of nursing in immunization. Descriptive documental and quantitative research. Utilized secondary data of hepatitis B, between 2001 and 2011 and vaccination coverage of hepatitis B vaccine between 1995 and 2011 in Paraná State, available in DATASUS, SINAN and Immunization Programs. Data has been collectedfrom May to July 2012. Included cases of hepatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
1
10
1
11
Order By: Relevance
“…Other research done in the country, also confirm the higher prevalence in adults, the age group between 20 and 40 as the most affected and that can relate to increased risk of infection through sexual intercourse. 6 Unlike the present study, we found a very small number of adolescents affected by hepatitis B, only three cases in the period of almost a decade.…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…Other research done in the country, also confirm the higher prevalence in adults, the age group between 20 and 40 as the most affected and that can relate to increased risk of infection through sexual intercourse. 6 Unlike the present study, we found a very small number of adolescents affected by hepatitis B, only three cases in the period of almost a decade.…”
Section: Resultscontrasting
confidence: 95%
“…12 The frequency found for children and adolescents in this study, was also low (5.3%), as well as in the survey conducted between 2001-2011, Paraná, who observed small values in the age group of zero to nine years, which It reflects the good response to immunization performed in children. Already, the higher age groups have higher incidences, both for non-vaccination in these ages, which were not initially covered by the vaccine basic calendar, which implemented the vaccine against HB, but also at higher risk of infection through sexual transmission, 6 as previously stated.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…This high influence stands out in the productive and sexually active age groups, corroborating some studies [20][21][22]. Sexual risk behavior coupled with other factors may contribute to the concentration of the disease in these age groups [23].…”
Section: Discussionsupporting
confidence: 84%
“…Estudos revelam a ocorrência de doenças imunopreveníveis em idosos, como pneumonia, influenza (2) , tétano (3) e hepatite B (4) . Muitos casos identificados apresentavam esquema vacinal incompleto ou inexistente (5) , demonstrando a necessidade de melhorar o acesso à vacinação para este grupo populacional.…”
Section: Introductionunclassified